Pendidikan Pondok Pesantren dalam Pembentukan Karakter di Pondok Pesantren Hikmatul Huda Salem Brebes - M. Ma`mun Farid Farihi (Institut Agama Islam Negeri Purwokerto, 2021)
The purpose of this paper is to research and describe the efforts of Islamic boarding schools in forming character in adolescents. The current problem is the character crisis that has hit the nation's children. One of the problems that often occurs repeatedly, when education has not been able to become social control and control the character or morality of students. While students are the pillars of the nation, so the term